Amnésia global transitória e endoscopia digestiva alta - Sílvia César; Sandra Perdigão (Sociedade Galega de Medicina Interna, 2014)
Transient Global Amnesia (TGA) was described for the first time more than 100 years ago and is an amnesic syndrome of sudden onset and complete remission within 24 hours. During the episode the patient's behavior is normal except for the repetitive questioning about his immediate circumstances. TGA may be associated with emotional experiences, pain, exercise, exposure to cold water and sexual intercourse. Minor diagnostic procedures precipitating TGA such as gastroscopy or colonoscopy have been reported. We present a patient who developed TGA after gastroscopy, a rare complication of this procedure.